From the Military Royal Academy to the Geology Department in the Institute of Geosciences of the Federal University of Rio de Janeiro: the trajectory of a mineralogical collection - Bastos, Cristina Moura; Rangel, Marcio Ferreira; Almeida, Cícera Neysi de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
This paper treats the formation of the mineral collection of the former National School of Engineering (ENE), which today is partially incorporated in the Museum of Geodiversity of the Institute of the Geosciences of the Federal University of Rio de Janeiro (IGEO/UFRJ). The collection was formed with material of the Werner Mineralogical Collection, transferred from the Royal Military Academy (ARM) for the inauguration of the Royal Museum (currently the National Museum) in 1818, leaving the ARM without minerals used in the practical teaching of Geology and Mineralogy classes of the Engineering course. In 1824, samples were requested in duplicate from the Museum for the Academy, constituting the initial nucleus of this mineralogical collection. This nucleus was expanded through purchase and donations, reaching more than 5.000 exemplars in 1883. As time went by, the Royal Military Academy has been given different names. In 1937, it was renamed as the National School of Engineering. During the military dictatorship, the IGEO/UFRJ received part of the mineralogical collection of the ENE. A new inventory, in the progress of elaboration, shows that the number of samples in the institution is less than 1,000 units. The location is not known of the rest of this collection, of great historical and scientific relevance.